2020
DOI: 10.1177/0333102420905317
|View full text |Cite
|
Sign up to set email alerts
|

Headaches in the medieval Medical School of Salerno

Abstract: Premise Headaches are a serious public health concern of our days, affecting about 50% of the world’s adult population. However, such a plague is not limited to the modern era, since ancient archaeological, written, religious and cultural evidences testify to countless attempts to face such disorders from medical, neurosurgical, psychological and sociological perspectives. Background Substantially, the Hippocratic and Galenic theories about headache physiopathology remained predominant up to the 17th century, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The main complaint of migraine patients is long-lasting pulsating pain, which is intractable in many cases thus leading to chronic stress and depression [3,13,14]. Known from ancient times [15], cannabinoids emerged recently as a promising analgesic approach to treat migraine pain [16][17][18]. In particular, cannabis, now legalized in many countries, has shown a therapeutic effect in migraine [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…The main complaint of migraine patients is long-lasting pulsating pain, which is intractable in many cases thus leading to chronic stress and depression [3,13,14]. Known from ancient times [15], cannabinoids emerged recently as a promising analgesic approach to treat migraine pain [16][17][18]. In particular, cannabis, now legalized in many countries, has shown a therapeutic effect in migraine [16,19].…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic review by Taggart et al, intravenous ketorolac has been recommended as a second-line drug in the management of migraine [ 26 ]. In this regard, the results of other studies have shown that ketorolac may take effect after 30 to 60 min [ 43 , 44 ]. Baratloo et al in their study examined the efficacy measurement of ketorolac in reducing the severity of the headache.…”
Section: Discussionmentioning
confidence: 97%